Rape Cases in Nepal: A Feministic Study - Rumdali , Nini Rema (Political Science Journal, 2025)
Our civilization is characterized by male-chauvinism. Through the lens of feminism, this qualitative study aims to empower women in our society who have been raped and slain. Women's social, political, and economic rights are also aided by feminism. Despite creating laws to prevent rape, the government consistently falls short in providing victims with safety and justice. Women in our culture are insecure. In the name of women's rights, WOREC Nepal and other human rights organizations have been successful, however the victims are still women. Instead of intending to send a writ to the courts, the mediators when the incident occurs encourage the victims and offenders to reach financial settlements. Using feminism as a lens, this article focuses heavily on rape episodes that happen in our society and attempts to educate readers on the laws that prohibit them.